2018
DOI: 10.1016/j.celrep.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Recently Identified Mutations in the Ebola Virus-Makona Genome Do Not Alter Pathogenicity in Animal Models

Abstract: Summary Ebola virus (EBOV), isolate Makona, the causative agent of the West African EBOV epidemic, has been the subject of numerous investigations to determine the genetic diversity and its potential implication for virus biology, pathogenicity, and transmissibility. Despite various mutations that have emerged over time through multiple human-to-human transmission chains, their biological relevance remains questionable. Recently, mutations in the glycoprotein GP and polymerase L, which emerged and stabilized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 41 publications
(77 reference statements)
4
82
0
Order By: Relevance
“…However, in vivo experiments have yet to unambiguously ascribe a pheno type to A82V and similar mutations in the context of pathogenesis. For instance, initial studies with Ifnar −/− immunodeficient laboratory mice and rhesus monkeys did not demonstrate an effect of A82V on disease severity or virus shedding 80 . This lack of an effect may be due to the true lack of effect of these mutations on pathogenesis, limitations of the in vivo studies (such as compensatory mutations for the A82V phenotype observed in vitro), or intrinsic differences among laboratory mice, NHPs and humans, such as infection cofactors or immune responses.…”
Section: Box 1 | Anthropology In Filovirus Disease Outbreak Controlmentioning
confidence: 99%
“…However, in vivo experiments have yet to unambiguously ascribe a pheno type to A82V and similar mutations in the context of pathogenesis. For instance, initial studies with Ifnar −/− immunodeficient laboratory mice and rhesus monkeys did not demonstrate an effect of A82V on disease severity or virus shedding 80 . This lack of an effect may be due to the true lack of effect of these mutations on pathogenesis, limitations of the in vivo studies (such as compensatory mutations for the A82V phenotype observed in vitro), or intrinsic differences among laboratory mice, NHPs and humans, such as infection cofactors or immune responses.…”
Section: Box 1 | Anthropology In Filovirus Disease Outbreak Controlmentioning
confidence: 99%
“…If there was indeed an increase in both EBOV transmissibility and virulence, then higher virulence is likely to have directly increased viral fitness, and in the absence of an evolutionary trade-off as only a single substitution was identified. However, these apparent changes in phenotype also coincided with the movement of the virus from Guinea to Sierra Leone, such that any change in case numbers and mortality could in fact be due to a change in epidemiological factors (such as access to health care or differing human demographics and/or transmission networks), and recent studies using animal models suggest that A82V has no direct impact on virulence 118 .…”
Section: Heritabilitymentioning
confidence: 99%
“…The magnitude of the West African EVD epidemic in 2013-2016 has stimulated speculation about possible changes in EBOV or its infectious process, which could have caused its rapid spread [32]. The documented case-fatality rate of the epidemic was not superior to that observed in other historical outbreaks [33], and a greater pathogenicity of EBOV Makona has also been reasonably ruled out in animal models [34,35].…”
Section: Discussionmentioning
confidence: 99%